2018
DOI: 10.1371/journal.pone.0190392
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare costs for the elderly in Japan: Analysis of medical care and long-term care claim records

Abstract: BackgroundThe population is aging rapidly in many developed countries. Such countries need to respond to the growing demand and expanding costs of healthcare (HC) for the elderly. Therefore, it is important to investigate the factors correlating such HC costs. In Japan, HC is composed of two sections, namely medical care (MC) and long-term care (LTC). While many studies have examined MC and LTC costs on their own, few studies have conducted comprehensive investigations of HC costs. The aim of this study is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 22 publications
0
16
1
2
Order By: Relevance
“…As noted by Akiyama et al (2018) and many others, with a rapidly ageing population, healthcare costs in Japan are on the rise. To combat these rising costs, the Japanese government has been attempting to reform the healthcare system by, inter alia, promoting clinical specialization and collaboration.…”
Section: Medical Expenditures In Japanmentioning
confidence: 94%
“…As noted by Akiyama et al (2018) and many others, with a rapidly ageing population, healthcare costs in Japan are on the rise. To combat these rising costs, the Japanese government has been attempting to reform the healthcare system by, inter alia, promoting clinical specialization and collaboration.…”
Section: Medical Expenditures In Japanmentioning
confidence: 94%
“…Combined with the existing research, it can be found that there are relatively few researches on the grading of disabled objects, and most of them are based on practical analysis. As an important part of disability scale measurement, the transition probability of disability state is the premise and foundation to promoting demand assessment and will help to plan the medical and social services needed in a timely manner (1)(2)(3) and to reduce the burden on the elderly and their families who cannot take care of themselves (4,5). First of all, regarding the evaluation indicators of incapacitated subjects (6)(7)(8), most studies use single-dimensional scales for measurement, such as the commonly used Barthel, Lawton, and Brody instrumental daily activity scales and the Katz Scale, and the international function/disability and health-grading ICF and InterRAI evaluation systems which are more commonly used in OECD countries (9,10).…”
Section: Literature Reviewmentioning
confidence: 99%
“…At present, a single-dimension scale is widely used in disability grading research (4). The main reason is that the single-dimension scale is becoming more and more perfect and has high reliability (24)(25)(26)(27)(28).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This adverse event can completely undermine the household budget economically and it is one of the main sources of financial risk for the population (Scott et al, 2018;Grépin et al, 2020). Households with older members requir-ing permanent long-term care are under greater risk (Akiyama et al, 2018). Usually the main method of managing household financial risks is mandatory health insurance (Hasegawa, 2017).…”
Section: Introductionmentioning
confidence: 99%